2021
DOI: 10.3389/fonc.2021.774017
|View full text |Cite
|
Sign up to set email alerts
|

PSMA PET Imaging in Glioblastoma: A Preclinical Evaluation and Theranostic Outlook

Abstract: BackgroundProstate specific membrane antigen (PSMA) PET imaging has recently gained attention in glioblastoma (GBM) patients as a potential theranostic target for PSMA radioligand therapy. However, PSMA PET has not yet been established in a murine GBM model. Our goal was to investigate the potential of PSMA PET imaging in the syngeneic GL261 GBM model and to give an outlook regarding the potential of PMSA radioligand therapy in this model.MethodsWe performed an 18F-PSMA-1007 PET study in the orthotopic GL261 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…However, the definition of a “significant uptake” remains undefined. In a preclinical study, Kirchner et al 56 confirmed a high TBR due to low expression in normal brain parenchyma, but a low absolute tumoral uptake. Similarly, some authors have highlighted that PSMA-based targeted therapy could be restricted because of a low target-to-liver ratio.…”
Section: Discussionmentioning
confidence: 93%
“…However, the definition of a “significant uptake” remains undefined. In a preclinical study, Kirchner et al 56 confirmed a high TBR due to low expression in normal brain parenchyma, but a low absolute tumoral uptake. Similarly, some authors have highlighted that PSMA-based targeted therapy could be restricted because of a low target-to-liver ratio.…”
Section: Discussionmentioning
confidence: 93%
“…Some case reports demonstrated promising results for the implementation of PSMA-targeted therapy in HGG [ 32 , 33 ]. A preclinical study has recently demonstrated that although PSMA-targeted PET in a specific murine model of glioblastoma is feasible and resulted in high TBR, absolute tumoral uptake values remained low limiting the applicability of this murine model for PSMA-targeted therapy [ 34 ]. Overall, further preclinical investigations are warranted to identify suitable models for preclinical evaluation of PSMA-targeted theranostic approaches in HGG, and further clinical studies using PSMA-targeted agents radiolabelled with alpha- or beta-emitting radionuclides are needed to confirm the value of PSMA-targeted theranostics in HGG.…”
Section: Discussionmentioning
confidence: 99%
“…PSMA avidity is detected in various nonprostatic benign and malignant conditions. 1,2 HO is a diverse pathologic process, characterized by formation of extraskeletal bone in any connective tissue such as the skeletal muscles, fascia, tendon, ligament, subcutis, skin, vascular wall, and so on. 3 The new bone formation in HO is associated with the inflammatory process and neovascularization, which are believed to contribute for PSMA uptake in HO.…”
Section: Figurementioning
confidence: 99%
“…This case demonstrates the incidental detected PSMA avidity in the HO. PSMA avidity is detected in various nonprostatic benign and malignant conditions 1,2 . HO is a diverse pathologic process, characterized by formation of extraskeletal bone in any connective tissue such as the skeletal muscles, fascia, tendon, ligament, subcutis, skin, vascular wall, and so on 3 .…”
mentioning
confidence: 99%